Mini-review and Meta-analysis of effort ratios in mixed martial arts rounds: key insights for research and coaches - Aleksandro Ferreira Gonçalves; Rafael Pereira Azevedo Teixeira; Clóvis Albuquerque Maurício; Diego Ignacio Valenzuela Pérez; Felipe Guimarães Teixeira; Eliane Ferraz Silva; Ciro José Brito; Bianca Miarka (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
This study investigated the critical aspect of match intensity in MMA bouts and its impact on performance. MMA is a physically demanding sport, and understanding the dynamics of intensity throughout matches is essential for both athletes and trainers. To achieve this goal, we adhered to the PRISMA guidelines for comprehensive and ethical reporting of our findings. We conducted a thorough search of electronic databases, including PubMed, Bireme, CINAHL, SportDiscus, EMBASE, SCOPUS, and Cochrane, to identify relevant articles. Our search terms included "mixed martial arts athletes," "movement time study," "male athletes," "female athletes," "lactate," "heart rate," and "motor action." Our meta-analysis yielded compelling results. We found a statistically significant difference between the third and second rounds (p=0.0001) for both total high-intensity and low-intensity time. Additionally, significant differences were observed when comparing the second round to the first round for total high-intensity time (p=0.52) and total low-intensity time (p=0.58). These findings indicate a progressive increase in intensity throughout the rounds, with the third round significantly affecting the fight's outcome. Our results suggest that trainers and athletes should consider a specific strategy for the third round to address potential metabolic fatigue. Future research should delve deeper into strategies that can effectively manage intensity throughout MMA bouts, with a focus on factors like nutrition, recovery, and psychological aspects, which could provide valuable insights into optimizing performance in this demanding sport.